2018
DOI: 10.1111/eea.12704
|View full text |Cite
|
Sign up to set email alerts
|

Food supplementation to optimize inoculative release of the predatory bug Macrolophus pygmaeus in sweet pepper

Abstract: Biological control is widespread in management of greenhouse sweet pepper crops. Several species of predatory mites, bugs, and parasitoids are used against a wide range of pest species. However, biological control of particular pests like aphids, caterpillars, and the tobacco whitefly, Bemisia tabaci Gennadius, remains problematic. Macrolophus pygmaeus Rambur (Hemiptera: Miridae) is a generalist predatory bug which is used on a large scale in Western European tomato greenhouses. It has already been demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 43 publications
0
18
1
7
Order By: Relevance
“…When pests are scarce or absent, it will turn to plant feeding and thus sustain a population that can prevent pest outbreaks . Introducing M. pygmaeus at the beginning of the season accompanied by a correct food supplementation strategy is sufficient to establish a population in sweet pepper greenhouses . Previous research has shown M. pygmaeus is capable of strongly reducing aphid population growth in sweet pepper, but complete control has not always been achieved …”
Section: Introductioncontrasting
confidence: 98%
See 3 more Smart Citations
“…When pests are scarce or absent, it will turn to plant feeding and thus sustain a population that can prevent pest outbreaks . Introducing M. pygmaeus at the beginning of the season accompanied by a correct food supplementation strategy is sufficient to establish a population in sweet pepper greenhouses . Previous research has shown M. pygmaeus is capable of strongly reducing aphid population growth in sweet pepper, but complete control has not always been achieved …”
Section: Introductioncontrasting
confidence: 98%
“…This requires a release strategy that is both effective and efficient. Brenard et al . developed an optimal release strategy for M. pygmaeus in sweet pepper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In greenhouse tomato crops, an optimal supplementation scheme consists of weekly food applications during 6–8 weeks, as this is the time it takes for a generation of M. pygmaeus to develop (Moerkens et al., ). In contrast to tomato, sweet pepper crops have pollen available for the bugs, but food supplementation is still required to reach a sufficiently high population at the start of the season and to ensure quick dispersal the food should be supplemented in a full‐field fashion (Brenard et al., ). Although full‐field food supplementation in sweet pepper yields the best results, growers are not always inclined to apply this method due to higher food and labour costs.…”
Section: Introductionmentioning
confidence: 99%